Profile of uncommon primary adult hepatic malignancies at a tertiary care center - Thomas, Eliz; Venkatasubramanian, A (Journal of Pathology of Nepal, 2020)
Background: Hepatocellular carcinoma has been the most common primary malignancy of the liver in adults, followed by cholangiocarcinoma. The less common malignancies are those arising from the vascular endothelial cells, neuroendocrine cells, hematolymphoid tissues, and mesenchymal tissues. Imaging studies alone may pose a diagnostic challenge, due to the variable appearances. Histological review of the tissue specimen along with immunohistochemical stains are imperative for diagnosis. However, a multidisciplinary approach is necessary to make an accurate diagnosis and help in management. Materials and methods: The unusual adult primary hepatic malignancies were studied in 2 years period with clinic-radiological and biochemical correlation and also the age and sex distribution were determined. Ethical approval was obtained. Statistical analysis used: SPSS version 23.0. Results: A total of 24 liver malignancies were encountered. Metastatic tumors and tumor-like lesions were excluded. The patient's clinico-radiological findings and laboratory investigations were noted. A total of 6 unusual non-hepatocellular malignancies were seen and identified based on morphology and special stains. Out of 6 non-hepatocellular malignancies, 3 were neuroendocrine carcinomas, 2 were leiomyosarcomas and 1 was a hematolymphoid malignancy. Radiologic impression and biochemical parameters helped arrive at a definitive opinion as the lesions were not typical of this location. A high index of suspicion along with the immunohistochemical profile finally facilitated the diagnosis. Conclusions: The cases of primary non-hepatocellular malignancies are unexpected. A multidisciplinary approach is mandatory.